PENERAPAN SAK EMKM PADA LAPORAN KEUANGAN RUMAH MAKAN ELOK KABUPATEN ALOR - Saku, Yunus Abraham; Hermelinda, Tuti (Universitas Ratu Samban, 2024)
The increasingly intense competition in the business world, especially the culinary business, spurs culinary business owners, especially restaurants to continue to maintain quality both in terms of service and management. One form of concern for these culinary business owners is to start implementing financial records correctly so that financial reports can be produced in accordance with established standards. Elok Restaurant is one of the many restaurants in Alor Regency. This study presents a form of financial statements based on SAK EMKM that can be used at Elok Restaurant in Alor Regency consisting of a Statement of Financial Position, Income Statement and Notes to Financial Statements. The method used in this research is descriptive Quantitative method with data collection techniques using literature study and field study